2019
DOI: 10.1039/c9cc04978a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient photocaging of a tight-binding bisubstrate inhibitor of cAMP-dependent protein kinase

Abstract: PKA bisubstrate inhibitor photocaging resulted in an over 5 orders of magnitude affinity difference between the photocaged and the active inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“… 175 177 The tail absorption of 8a in the visible range (398–440 nm) was sufficient to promote the photoreaction. 175 , 178 Introducing electron-donating groups (EDG) at the 7-position of NDBF ( 8b and 8c ) led to a bathochromic shift in λ max abs but also reduced its photouncaging quantum efficiency ( Table 4 ). 151 , 174 The low quantum yield of 8c was attributed to a charge-transfer transition following photoexcitation that competes with LG release.…”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“… 175 177 The tail absorption of 8a in the visible range (398–440 nm) was sufficient to promote the photoreaction. 175 , 178 Introducing electron-donating groups (EDG) at the 7-position of NDBF ( 8b and 8c ) led to a bathochromic shift in λ max abs but also reduced its photouncaging quantum efficiency ( Table 4 ). 151 , 174 The low quantum yield of 8c was attributed to a charge-transfer transition following photoexcitation that competes with LG release.…”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 99%
“… However, due to the reduction in quantum efficiency, the uncaging cross section (Φ r ε­(λ irr )) of the latter group tends to be comparable to that of the parent oNB 5a . ,, Nitrodibenzofuran 8a (NDBF; Figure ), introduced by Ellis-Davies and co-workers, is an exceptional red-shifted oNB derivative that releases LGs efficiently . The photolysis of ether, thioether, and phosphoester , LGs caged with this group reportedly proceeded with Φ r values of 0.5–0.7, although lower quantum yields were obtained in some cases (0.04–0.2). The tail absorption of 8a in the visible range (398–440 nm) was sufficient to promote the photoreaction. , Introducing electron-donating groups (EDG) at the 7-position of NDBF ( 8b and 8c ) led to a bathochromic shift in λ max abs but also reduced its photouncaging quantum efficiency (Table ). , The low quantum yield of 8c was attributed to a charge-transfer transition following photoexcitation that competes with LG release. , Ball and co-workers recently reported that derivatives of 8a and 8c undergo efficient photocleavage of C­(sp 2 )–N bonds .…”
Section: Photorelease From Organic Photoactivatable Compoundsmentioning
confidence: 99%
“…The inhibitory properties of the potent bi‐substrate inhibitor 2 of cAMP‐dependent protein kinase (PKAcα) was masked by the inclusion of a nitrodibenzofuran (NDBF)‐derived caging group onto the nitrogen atom of the pyrimidine heterocycle, preventing key hydrogen bond interactions from occurring in the ATP binding site (Figure 2). [8] The binding affinity of the caged inhibitor 1 for PKAcα was 1900 nM K D . Irradiation of the caged inhibitor using a Hg vapour lamp resulted in a significant decrease in affinity for PKAcα by 5‐orders of magnitude ( K D <0.1 nM).…”
Section: Light‐responsive Kinase Inhibitorsmentioning
confidence: 98%
“…An example of a photocaged bisubstrate inhibitor ( Figure 1 a) of protein kinases (PKs) was recently published by our group [ 22 ]. PKs are transferases that catalyze protein phosphorylation, a key reaction of regulation of cell’s life.…”
Section: Introductionmentioning
confidence: 99%
“…The conjugation of the fragments yields inhibitors with a remarkable potency, where the lowest K D values of ARCs are in the low picomolar range. The attachment of a single nitrodibenzofuran (NDBF) photocage to a hot-spot position on the ATP-binding site-targeting fragment efficiently blocked the binding of ARC to the catalytic subunit type α of cAMP-dependent PK (PKAcα), as shown by the five orders of magnitude affinity difference between the photocaged ( K D = 1.9 µM) and active ( K D = 5 pM) forms of the inhibitor [ 22 ]. Furthermore, several examples of bivalent (and multivalent) ligands have been published whose multivalent binding is controlled by a photoswitch ( Figure 1 d) [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%